Increased and Decreased Superficial White Matter Structural Connectivity in Schizophrenia and Bipolar Disorder. (6th April 2019) - Ji, Ellen; Guevara, Pamela; Guevara, Miguel; Grigis, Antoine; Labra, Nicole; Sarrazin, Samuel; Hamdani, Nora; Bellivier, Frank; Delavest, Marine; Leboyer, Marion; Tamouza, Ryad; Poupon, Cyril; et al.
Abstract: Schizophrenia (SZ) and bipolar disorder (BD) are often conceptualized as "disconnection syndromes, " with substantial evidence of abnormalities in deep white matter tracts, forming the substrates of long-range connectivity, seen in both disorders. However, the study of superficial white matter (SWM) U-shaped short-range tracts remained challenging until recently, although findings from postmortem studies suggest they are likely integral components of SZ and BD neuropathology. This diffusion weighted imaging (DWI) study aimed to investigate SWM microstructure in vivo in both SZ and BD for the first time. We performed whole brain tractography in 31 people with SZ, 32 people with BD and 54 controls using BrainVISA and Connectomist 2.0. Segmentation and labeling of SWM tracts were performed using a novel, comprehensive U-fiber atlas. Analysis of covariances yielded significant generalized fractional anisotropy (gFA) differences for 17 SWM bundles in frontal, parietal, and temporal cortices. Post hoc analyses showed gFA reductions in both patient groups as compared with controls in bundles connecting regions involved in language processing, mood regulation, working memory, and motor function (pars opercularis, insula, anterior cingulate, precentral gyrus). We also found increased gFA in SZ patients in areas overlapping the default mode network (inferior parietal, middle temporal, precuneus), supporting functional hyperconnectivity of this network evidenced in SZ. We thus illustrate that short U-fibers are vulnerable to the pathological processes in major psychiatric illnesses, encouraging improved understanding of their anatomy and function.